Research on the Mechanism and Prevention of Hypertension Caused by Apatinib Through the RhoA/ROCK Signaling Pathway in a Mouse Model of Gastric Cancer - Wang, Wenjuan; Li, Caie; Zhuang, Chenchen; Zhang, Haodong; Wang, Qiongying; Fan, Xin; Qi, Miaomiao; Sun, Runmin; Yu, Jing (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is one of the main adverse effects of antiangiogenic tumor drugs and thus limits their application. The mechanism of hypertension caused by tyrosine kinase inhibitors (TKIs) targeting vascular endothelial growth factors is mainly related to inhibition of the nitric oxide (NO) pathway and activation of the endothelin pathway, as well as vascular rarefaction and increased salt sensitivity; consequently, prevention and treatment differ for this type of hypertension compared with primary hypertension. Apatinib is a highly selective TKI approved in China for the treatment of advanced or metastatic gastric cancer. The RhoA/ROCK pathway is involved in the pathogenesis of hypertension and mediates smooth muscle contraction, eNOS inhibition, endothelial dysfunction and vascular remodeling. In this study, in vivo experiments were performed to explore whether the RhoA/ROCK signaling pathway is part of a possible mechanism of apatinib in the treatment of gastric cancer-induced hypertension and the impairment of vascular remodeling and left ventricular function. Y27632, a selective small inhibitor of both ROCK1 and ROCK2, was combined with apatinib, and its efficacy was evaluated, wherein it can reduce hypertension induced by apatinib treatment in gastric cancer mice and weaken the activation of the RhoA/ROCK pathway by apatinib and a high-salt diet (HSD). Furthermore, Y-27632 improved aortic remodeling, fibrosis, endothelial dysfunction, superior mesenteric artery endothelial injury, left ventricular dysfunction and cardiac fibrosis in mice by weakening the activation of the RhoA/ROCK pathway. The expression of RhoA/ROCK pathway-related proteins and relative mRNA levels in mice after apatinib intervention were analyzed by various methods, and blood pressure and cardiac function indexes were compared. Endothelial and cardiac function and collagen levels in the aorta were also measured to assess vascular and cardiac fibrosis and to provide a basis for the prevention and treatment of this type of hypertension.